Solar water heating system in libyan buildings - Ali Almukhtar, Isa (2015)
Solar energy is a clean and abundant energy resource that can be used to supplement several energy needs. Solar energy can be utilized as a form of heat, such as solar water heating, and as electricity, such as solar photovoltaic. Solar water heating systems are commonly referred to in the industry as Solar Domestic Hot Water systems. The challenges (increasing demand for energy, sustainable development, low competitiveness, reducing environmental impacts) and the opportunities (value added, job creation, transfer of knowledge and technology acquisition) that North African countries are experiencing today in this field, call for collective action across the whole region, oriented towards tangible results, including Libya faces challenges in providing energy in light of the continuing power outages. The objectives of this research are to identify the current practices of solar water heating system in Libyan buildings, to identify the factors that hinder the application of solar water heating system in Libyan buildings, to suggest on the application of solar water heating system in Libyan buildings. Questionnaires were used to collect the data from contractors and consultants in the construction industry. Ranking and analysis of variance (correlation) were used to analyse the data collected with the use of version 21 SPSS. It was found that the application of renewable energy in construction project is very low. However, the factors that hinder of solar water heating system in Libya were lack of consultant's initiatives, lack of financial commitment, and lack of commitment design team, lack of government interest to promote solar water heating system and high tax on solar energy by government. The result of this finding implicate that the construction industry in Libya need to improve its approach in using solar water heating system by understanding its current practices and finding ways to solve of the factors that hinder.